Aesthetic Imagination in the Literacy-based Music Classroom: Implications for School Policy and Practice - Harris, Carol (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1996)
Ministry statements regarding music programming tend to be couched either in vague generalities or as conflicting directives for implementation. The aesthetic imagination of students suffers the first loss in school boards that elect to place the responsibility for music in the hands of untrained teachers. This paper traces imagination as emanating from an inextricable combination of impression, sensual perception, ideas, and intentional expression. Imagination itself is examined here first, as heightened perception, and second, as phenomena "becoming." As expression must have substantive material for its realization, music education should include the skills both of performance and of literacy. Anything less denies students, especially the disadvantaged, "voice" and exacerbates the present state of cultural inequality.